Hydro-Distilled and Supercritical Fluid Extraction of Essential Oil: Characterization of Bioactives Along With Antioxidant, Antimicrobial and Antibiofilm Activities - Ali Abbas; Farooq Anwar; Safar M. Alqahtani; Naveed Ahmad; Samiah H. Al-Mijalli; Muhammad Shahid; Munawar Iqbal (SAGE Publishing, 2022)
Present research work evaluates variation in volatile chemicals profile and biological activities of essential oil (EO) obtained from the leaves of eucalyptus ( Eucalyptus camaldulensis Dehnh.) using hydro-distillation (HD) and supercritical fluid extraction (SFE). The yield (1.32%) of volatile oil by HD was higher than the yield (.52%) of the SFE method ( P < .05). The results of physical factors like density, color, refractive index, and solubility of the EOs produced by both the methods showed insignificant variations. Gas chromatography - mass spectrometry (GC-MS) compositional analysis showed that eucalyptol (31.10% and 30.43%) and α -pinene (11.02% and 10.35%) were the main constituents detected in SFE and HD extracted Eucalyptus camaldulensis EO, respectively. Antioxidant activity-related parameters, such as reducing ability and DPPH free radical scavenging capability exhibited by EO obtained via SFE were noted to be better than hydro-distilled EO. Supercritical fluid extracted and hydro-distilled essential oils demonstrated a considerable but variable antimicrobial potential against selected bacterial and fungal strains. Interestingly, oil extracted by SFE showed relatively higher hemolytic activity and biofilm inhibition potential. The variation in biological activities of tested EOs can be linked to the difference in the volatile bioactives composition due to different isolation techniques. In conclusion, the EO obtained from Eucalyptus leaves by the SFE method can be explored as a potential antioxidant and antimicrobial agent in the functional food and nutra-pharmaceutical sector.